Tingkat underpricing saham syariah dan non syariah saat IPO dan faktor-faktor yang mempengaruhinya - Lia Hidayah; Sunarsih Sunarsih (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2022)
Underpricing is a condition where the stock price of a company when conducting an Initial Public Offering (IPO) is below the stock price when it is in the secondary market. In Indonesia, shares are divided into two types, namely Islamic shares and non-Sharia shares. This study aims to determine the effect of underwriter reputation, investment risk, profitability, financial leverage, and company size on the level of underpricing of Islamic stocks and non-Islamic stocks. The sampling technique used is purposive sampling. The analytical method used is multiple linear regression with cross section data type. The results of the study found that there were differences that affected the underpricing of Islamic and non-Islamic stocks. In Islamic stocks, underpricing is only influenced by financial leverage, while underpricing for non-Sharia stocks is influenced by investment risk and company size. This study provides an overview to investors who have the aim of investing in companies that are IPOs for profit so that they carefully consider the influence of underwriter variables, investment risk, company size, financial leverage, and profitability. For companies, this research provides an overview for companies so that they can make the right decisions in offering optimal share prices. And for further researchers, these findings can be used as a reference to be able to do better research in the future.